Exploring research trends in healthcare asset management systems - Stanimirović, Dalibor (Medicine, law & society, 2025)
Asset Management Systems (AMS) are increasingly recognized for their potential to enhance operational efficiency, cost-effectiveness, and sustainability across assetintensive sectors. In healthcare, however, the implementation of AMS remains fragmented, despite mounting pressures to improve medical equipment usage, infrastructure reliability, and service delivery. This study presents a literature review supported by a bibliometric analysis of 248 documents on AMS research in healthcare, published up to 2024 and indexed in the Scopus database, examining the evolution of AMS research with a specific focus on healthcare applications. Using Python and VOSviewer, the bibliometric analysis focuses on scientific production, geographical coverage, and major research clusters. The findings highlight a growing global interest in AMS and indicate a broader shift toward digitalization and strategic integration within healthcare systems. We synthesize these insights into a set of key areas and priorities, offering evidence-based recommendations to support more effective AMS adoption in healthcare.
Keywords: asset management system; bibliometric analysis; bibliometrična analiza; healthcare; medical equipment; medicinska oprema; raziskovalni trendi; research trends; sistem za upravljanje sredstev; zdravstvena oskrba